A novel SPTB variant in a Cambodian child with hereditary spherocytosis without a family history - Chean Sophâl; Kim Leanghay; Chin Soey (Pediatric Hematology Oncology Journal, 2025)
Background: Hereditary spherocytosis (HS) is a form of congenital hemolytic anemia resulting from red cell membrane protein deficiency. Most cases (75 %) will have a family history of HS, but for those with no family history, there may be a delay in diagnosis. Case report: Herein, we report a 3 ½ years old boy of Cambodian origin who presented with anemia, jaundice, and hepato-splenogaly with no family history of hemolysis. The blood film showed spherocytosis and polychromasia with a negative direct agglutination test (DAT). Genomic DNA analysis of the SPTB gene (NM_001355436.2) revealed a novel, unreported heterozygous variant, c.1720dup, (p.Glu574GlyfsTer3), confirming as de novo variant and caused HS. Treatment focuses on supportive care, including folic acid supplementation and transfusion as needed. Conclusion: This is the first case report of HS resulting from a novel heterozygous SPTB variant in Cambodia. HS should be considered in the differential diagnosis of hemolytic anemia, regardless of the patient's ethnic background.